Pengaruh educational support dan gender stereotype terhadap entrepreneurship behavior (Studi kasus: Program Wirausaha Merdeka) - Dewantara, Norman; Rai, Ni Gusti Made; Noer, Lissa Rosdiana (Universitas Tarumanagara, 2024)
Entrepreneurship has an important role in creating jobs. The government of Indonesia has supported the existence of development facilities in the field of entrepreneurship through the Wirausaha Merdeka Program. This research model is built based on the Theory of Planned Behavior combined with educational support and gender stereotypes as antecedent variables. The results of this study show that educational support influences entrepreneurship intention mediated by attitude towards entrepreneurship, perceived behavioral control, and subjective norms. However, this study does not find any influence of gender stereotypes on entrepreneurship intention. This study also finds a relationship between entrepreneurship intention and entrepreneurship behavior. This program provides equal opportunities for women and men to develop skills and knowledge so that everyone feels confident to become an entrepreneur. The government of Indonesia also needs to build partnerships with business networks, such as investors to help fund business. Thus, educational support will have an impact on increasing the number of entrepreneurs. Kewirausahaan memiliki peranan penting dalam menciptakan lapangan kerja. Pemerintah Indonesia telah mendukung adanya sarana pengembangan di bidang kewirausahaan melalui program Wirausaha Merdeka. Model penelitian ini dibangun berdasarkan Theory of Planned Behavior yang dikombinasikan dengan educational support dan gender stereotype sebagai variabel anteseden. Hasil penelitian ini menunjukkan bahwa educational support berpengaruh terhadap entrepreneurship intention yang dimediasi oleh attitude towards entrepreneurship, perceived behavioral control, dan subjective norms. Namun, penelitian ini tidak menemukan adanya pengaruh gender stereotype terhadap entrepreneurship intention. Penelitian ini juga menemukan hubungan antara entrepreneurship intention terhadap entrepreneurship behavior. Program ini memberikan kesempatan yang sama bagi perempuan dan laki-laki dalam mengembangkan keterampilan dan pengetahuan, sehingga setiap individu merasa percaya diri untuk menjadi wirausaha. Pemerintah Indonesia perlu membangun kemitraan dengan jaringan usaha, seperti investor untuk membantu pendanaan usaha. Dengan demikian, dukungan pendidikan akan berdampak pada peningkatan jumlah wirausaha.